2014
DOI: 10.1111/ajt.12501
|View full text |Cite
|
Sign up to set email alerts
|

Liver Perfusion Changes Occurring During Pancreatic Islet Engraftment: A Dynamic Contrast-Enhanced Magnetic Resonance Study

Abstract: The aim of this study was to investigate liver microvascular adaptation following the intraportal infusion of pancreatic islets (pancreatic islet transplantation [islet-tx]) in diabetic patients using dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI). DCE-MRI was performed before and 7 days after islet-tx in six diabetic patients. Initial area under curve (AUC60) and volume transfer coefficient (Ktrans) were assessed as markers of liver perfusion. Clinical and metabolic monthly follow-up was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Another possibility to quantify perfusion with MRI is dynamic contrast-enhanced (DCE). It has, for example, been used to assess perfusion both in native pancreas in response to a glucose challenge [16] and in the setting of islets transplantation [17]. However, DCE-MRI requires the intravenous administration of a contrast agent (often gadolinium-based).…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility to quantify perfusion with MRI is dynamic contrast-enhanced (DCE). It has, for example, been used to assess perfusion both in native pancreas in response to a glucose challenge [16] and in the setting of islets transplantation [17]. However, DCE-MRI requires the intravenous administration of a contrast agent (often gadolinium-based).…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies have demonstrated the usefulness of the extended Kety model for studying liver tumors, in which the predominant blood supply comes from the hepatic arterial blood flow. (23)(24)(25) Possible correlations of pharmacokinetic parameters based on the two compartments with arterial and venous blood flows with histopathologic microvascular parameters should be the focus of future studies.…”
Section: Discussionmentioning
confidence: 99%
“…It also takes consideration of the fact that the concentration of contrast agent varies as time progresses, and acknowledges the exchange process of contrast agent inside and outside the vessels, thus describing certain hemodynamics information quantitatively, such as the generation and permeability of carcinoma capillaries (15). This technology has been applied to the grading and effect evaluation of certain malignant tumors, including glioma, breast carcinoma and prostate carcinoma (16)(17)(18). By analyzing variations in surrounding parameter values of a DCE-MRI pharmacokinetics model in patients with esophageal squamous carcinoma prior to and following chemoradiotherapy, the present study aimed to investigate the assessment and predictive abilities of an early response in primary esophageal carcinoma patients undergoing concurrent chemoradiotherapy.…”
Section: Discussionmentioning
confidence: 99%